Missing child cases in Sussex and West Mercia: predicting persistent runaways - Koster, Claire Emma Rosalie (2020)
A child goes missing every five minutes in the UK, exposing them to dangerous circumstances and severe consequences. This study aims to discover what variables might predict the transition from one-time (low risk) to repeat (high risk) runaway episodes in Sussex and West Mercia. A large anonymised dataset was provided by the Sussex and West Mercia police forces, consisting of 1,188 missing child cases, of which 1,158 had run away from home in these regions between 1st November 2016 and 28th February 2017. Using an exploratory approach, Chi squared analyses and a binary logistic regression were carried out in order to determine what factors were most significantly associated with runaway risk. These analyses resulted in a final 7-factor model: being in social services care, being known to the Youth Offending Services, being above the age of 12 years, having a criminal record, substance abuse, child sexual exploitation and family discord. This 7-factor model resulted in an accurate classification of 70% of cases. In order to better protect children by preventing repeat runaway episodes, this model should be applied in addition to current methods to better classify children as low risk or high risk. These suggestions are discussed further.